Self-Efficiency in the Field of Entrepreneurship Technology Program Students at UTHM - Aliashak, Mohamad Khairi; Rozali, Mohd Zulfadli (Research and Innovation in Technical and Vocational Education and Training, 2023)
Self-efficacy in the field of entrepreneurship is a catalyst factor for UTHM’s technology program students. This is especially true for students who have an interest in the field of entrepreneurship through the factors of empathy, motivation, and social support. This study aims to examine self-efficacy factors in the field of entrepreneurship of technology program students. This questionnaire-based survey was conducted, and data from 422 respondents were analyzed using descriptive statistics involving mean values and standard deviations as well as Mann-Whitney U and Spearman's Rank-Order Correlation tests. The findings of the study show that the self-efficacy factor in the field of entrepreneurship is high in the experience of students majoring in technology at UTHM. In addition, the results of the analysis show that there is no significant difference in the self-efficacy factor in the field of entrepreneurship between male and female students in the field of entrepreneurship as well as a significant strong relationship with the involvement of students majoring in technology at UTHM. This study can help stakeholders such as the Ministry of Higher Education, UTHM, and the technopreneur center in empowering this field of entrepreneurship more holistically and comprehensively. In conclusion, this research can enhance the participation of technology students on campus meanwhile they also can improve knowledge in the field of entrepreneurship